2021
DOI: 10.1186/s41935-020-00215-1
|View full text |Cite
|
Sign up to set email alerts
|

Stature estimation from handprint measurements: an application to the medicolegal investigation

Abstract: Background The estimation of the stature of human beings is a major part of medicolegal investigation when only body parts are found. The study aimed to estimate the stature from different handprint measurements in a Bangladeshi population using statistical considerations. A sample of 200 young Bangladeshi adults (100 men and 100 women) with no physical disabilities participated in this study. Stature and seven anthropometric measurements were measured using standard anthropometric measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…confession, testimony, video surveillance, physical evidence plays a pivotal role. For human identification, important parameters used are stature, gender, age and race, also known as the "Big Four" and stature is considered the most important in the "Big Four" for the development of biological profiles [6]. Researchers have shown that stature can be estimated from the hand [7], handprint [8], foot [9], 2D footprint [10], 3D footprint [11], dynamic footprint [12], fingerprint [13], and bones [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…confession, testimony, video surveillance, physical evidence plays a pivotal role. For human identification, important parameters used are stature, gender, age and race, also known as the "Big Four" and stature is considered the most important in the "Big Four" for the development of biological profiles [6]. Researchers have shown that stature can be estimated from the hand [7], handprint [8], foot [9], 2D footprint [10], 3D footprint [11], dynamic footprint [12], fingerprint [13], and bones [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The field of forensic science focuses on the examination and analysis of physical evidence found at crime scenes. This evidence may appear in either visible or latent forms, viz., impression evidence, which includes fingerprints, handprints, and footprints (Abderrahmane et al 2021, Asadujjaman et al 2021. However, other sorts of impression evidence may be helpful in a forensic investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have been done on the estimation of height using various measurements of teeth and skull:[ 7 ] Footprint measurements in Bangladeshi adults,[ 11 ] forearm length in North Karnataka population,[ 6 ] maxilla and facial measurements in a Indian population,[ 12 ] intermastoid distance,[ 1 ] long bones of American white and negros,[ 13 ] and from hand and foot measurements in a rare tribe of Kerala state in India. [ 13 14 ] The extensive knowledge and experience of our research team have been translated into high quality publications. [ 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 ] The present study was taken with an aim to investigate the stature estimation using head circumference and to derive the linear regression formula and to prove head circumference is a reliable source for stature estimation.…”
Section: Introductionmentioning
confidence: 99%